The cult of Saint Gabriel of Slutsk and its reflection in the narratives of the turn of the 19th–20th centuries - Koronevskii, Viktor I. (Journal of the Belarusian State University. History, 2024)
The article considers the political and symbolic aspect of the cult of Saint Gabriel of Slutsk in the late 19th – early 20th century. On the basis of analysing the collections of sources which have different origins (journalism, hagiography, hymnography), three narrative traditions of the perception of the martyr figure are distinguished. Those are Grodna, Minsk, and conditionally distinguished anti-Jewish, to which the researchers of the cult of the saint most often pay attention. The genesis of the three traditions and their relation to each other is studied. The author substantiates the point of view, according to which dioceses Gabriel was perceived as a local saint in the lands of Minsk and Grodna during the mentioned period. The fact affirms the belonging of the population of this territory to the Orthodox Church. It is noted that the Grodna and Minsk narrative traditions did not compete with each other and mutually complemented each other. They almost did not intersect with the antiJewish narrative, which was constructed by individual radical publicists from other regions of the Russian Empire.